2018
DOI: 10.1007/s11892-018-1070-9
|View full text |Cite
|
Sign up to set email alerts
|

Vegetarian Diets and the Risk of Diabetes

Abstract: Purpose of ReviewWorldwide, diabetes has increased steadily and in recent years, drastically. The majority of diabetes cases are type 2 (T2DM), caused by modifiable risk factors such as diet. Vegetarian diets have been studied over the past few decades for their preventative and therapeutic effects on diabetes and may be more beneficial than medication for diabetes management.Recent FindingsA vegetarian diet characterized by whole plant foods is most beneficial for diabetes prevention and management.SummaryVeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 28 publications
0
62
1
9
Order By: Relevance
“…In fact, the literature about any of the alternative diets (vegan, semi-vegetarian, etc.) is not very extensive [ 24 ].…”
Section: Mediterranean Diet and Other Healthy Diets Effects On Thementioning
confidence: 99%
“…In fact, the literature about any of the alternative diets (vegan, semi-vegetarian, etc.) is not very extensive [ 24 ].…”
Section: Mediterranean Diet and Other Healthy Diets Effects On Thementioning
confidence: 99%
“…Many previous studies have suggested that vegetarian diet may prevent the development of T2DM and improve insulin resistance [ 4 6 ]. A systematic study in Harvard T.H.…”
Section: Introductionmentioning
confidence: 99%
“…Vegetarianism refers to a kind of diet in which animal-based foods in particular meat and poultry are mainly eliminated from the diet. Based on the type of products consumed, it is divided into veganism (merely plant-based foodstuffs are used), lacto vegetarianism (plant foods and dairy supplies consumption), lacto-ovo vegetarianism (plant foods, dairy supplies, and egg consumption), and pesco-vegetarianism (plant foods, dairy supplies, egg, and fish consumption) [ 1 2 ]. A subdivision of veganism called “raw veganism” is a diet, which consists of plant-derived foods – without any animal products – that are not exposed to heat higher than approximately 118°F [ 3 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the literature suggests that a healthy diet leads to lower risks of many diseases such as obesity, cardiovascular disease, type 2 diabetes, and gestational diabetes, most of which have been proven to be associated with certain periodontal conditions [ 6 8 9 10 ]. The majority of studies conducted on vegetarianism and its divisions have been on the body's general health [ 2 10 ]. Studies evaluating the association of vegetarianism and oral condition are scarce and their focus has been the assessment of tooth condition and salivary factors A limited number of these studies have assessed the correlation between vegetarianism and the periodontal condition [ 11 ].…”
Section: Introductionmentioning
confidence: 99%